Asymmetry and Heterogeneity: Part and Parcel in Cardiac Autonomic Innervation and Function - Zandstra, Tjitske E.; Notenboom, Robbert G. E.; Wink, Jeroen; Kiès, Philippine; Vliegen, Hubert W.; Egorova, Anastasia D.; Schalij, Martin J.; De Ruiter, Marco C.; Jongbloed, Monique R. M. (Frontiers in Physiology, 2021)
The cardiac autonomic nervous system (cANS) regulates cardiac adaptation to different demands. The heart is an asymmetrical organ, and in the selection of adequate treatment of cardiac diseases it may be relevant to take into account that the cANS also has sidedness as well as regional differences in anatomical, functional, and molecular characteristics. The left and right ventricles respond differently to adrenergic stimulation. Isoforms of nitric oxide synthase, which plays an important role in parasympathetic function, are also distributed asymmetrically across the heart. Treatment of cardiac disease heavily relies on affecting left-sided heart targets which are thought to apply to the right ventricle as well. Functional studies of the right ventricle have often been neglected. In addition, many principles have only been investigated in animals and not in humans. Anatomical and functional heterogeneity of the cANS in human tissue or subjects is highly valuable for understanding left- and right-sided cardiac pathology and for identifying novel treatment targets and modalities. Within this perspective, we aim to provide an overview and synthesis of anatomical and functional heterogeneity of the cANS in tissue or subjects, focusing on the human heart.